Transactional Leadership Style, Organizational Justice And Employee Empowerment to Employee Organizational Commitments in the Yogyakarta Social Service - Mariana Ari (Green Publisher Indonesia, 2021)
This study aims to explain transactional leadership, organizational justice and employee empowerment towards employee organizational commitment in the Yogyakarta Social Service office. In this study, the research uses a quantitative approach because the analysis is based on existing theories and is related to the research topic. The theories used by researchers are Transactional leadership theory, Organizational Justice, Employee Empowerment and Organizational Commitment. The sample used was as many as 50 people who were determined by the saturated sample method. The data collection technique used was a questionnaire. The analysis technique used is simple regression with a significant level of 0.05. The results showed that (1) variable, transactional leadership has a positive and significant effect on organizational commitment (2) organizational justice has positive and significant impact on organizational commitment (3) employee empowerment has an effect positive and significant towards organizational commitment. Companies should pay attention to transactional leadership, organizational justice and employee empowerment to increase organizational commitment (4) taransactional leadership, organizational justice and employee empowerment simultaneously towards organizational commitment